2019
DOI: 10.3390/ijms20184563
|View full text |Cite
|
Sign up to set email alerts
|

FGFR Signaling as a Candidate Therapeutic Target for Cancers Resistant to Carbon Ion Radiotherapy

Abstract: Radiotherapy is an essential component of cancer therapy. Carbon ion radiotherapy (CIRT) promises to improve outcomes compared with standard of care in many cancers. Nevertheless, clinicians often observe in-field recurrence after CIRT. This indicates the presence of a subset of cancers that harbor intrinsic resistance to CIRT. Thus, the development of methods to identify and sensitize CIRT-resistant cancers is needed. To address this issue, we analyzed a unique donor-matched pair of clinical specimens: a trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 27 publications
(40 reference statements)
0
17
0
Order By: Relevance
“…Previously, we observed amplification of FGFR2 in radiotherapyresistant UCC [32] and FGFR3 mutations in UCC that recurred after carbon ion radiotherapy [33]; this suggests an essential role for the FGFR signaling pathway in UCC radio resistance, possibly via downstream surviving signals such as the PI3K/AKT pathways. Although the function of FGFR mutations remains unknown, inhibitors or FGF trap molecules may be effective [34] if the mutations are gain-of-function mutations.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Previously, we observed amplification of FGFR2 in radiotherapyresistant UCC [32] and FGFR3 mutations in UCC that recurred after carbon ion radiotherapy [33]; this suggests an essential role for the FGFR signaling pathway in UCC radio resistance, possibly via downstream surviving signals such as the PI3K/AKT pathways. Although the function of FGFR mutations remains unknown, inhibitors or FGF trap molecules may be effective [34] if the mutations are gain-of-function mutations.…”
Section: Discussionmentioning
confidence: 70%
“…The TaqMan RNase P Detection Reagents kit (Thermo Fisher Scientific, Waltham, MA, USA) was used to examine the degree of DNA fragmentation by comparing DNA concentrations measured by quantitative PCR using two different primer sets designed to amplify short (87 bp) and long (256 bp) amplicons of the RNase P gene [21]. The PapiPlex PCR method (GeneticLab Co., Ltd., Sapporo, Japan) was used for HPV typing to detect genotypes 6,11,16,18,30,31,33,35,39,45,51,52,56,58,59, and 66.…”
Section: Tissue Sample Collection Dna Preparation and Hpv Typingmentioning
confidence: 99%
“…Beyond playing an important role in CNS embryonal development, FGFR signaling influences angiogenesis and tumor cell migration, differentiation, proliferation, and survival. Not surprisingly, FGFRs have emerged as a major target for cancer therapeutics across tumor types and multiple targeting strategies are under investigation [5,13,16,19,24,30,47,48].…”
Section: Introductionmentioning
confidence: 99%
“…In their case study, Darwis and coworkers [2] observed an enrichment of somatic mutations in FGFR3 and FGFR4 genes in the CIRT-recurrent tumor compared with the treatment-naïve tumor. The authors showed that the FGFR inhibitor could sensitize multiple cancer cell lines to carbon ions at 3 Gy (RBE: relative biological effectiveness), the daily dose prescribed to the patient.…”
mentioning
confidence: 98%
“…In this special issue of the International Journal of Molecular Sciences, "Counteracting Radioresistance Using the Optimization of Radiotherapy", several studies have been published addressing some of the aspects related to tumor radio-resistance, with one research article [1], two communication articles [2,3], one review article [4] and one technical note [5].…”
mentioning
confidence: 99%